EXPLORING RESTLESS LEGS SYNDROME AND QUALITY OF LIFE HEMODIALYSIS CKD PATIENTS THROUGH COMPREHENSIVE SCREENING - Muzani Shopa; Nurhusna Nurhusna; Yulia Indah Permata Sari (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2026)
Introduction: Restless Legs Syndrome is a common neurological disorder among chronic kidney disease patients undergoing hemodialysis, significantly affecting their physical and psychological quality of life. In Indonesia, studies on this association remain limited. This study uniquely employed the CH-RLSQ13 screening tool to provide a more comprehensive and standardized RLS diagnosis.Methods: This study used a quantitative design with a cross-sectional approach. The sample was taken by total sampling using the CH-RLSQ13 screening, obtained 43 CKD patients with RLS who underwent hemodialysis at Raden Mattaher Jambi Hospital. Data were collected using IRLSSG questionnaire for RLS level and RLSQoL for quality of life. Data were analyzed using Spearman correlation test (p < 0.05).Results: Most of the respondents experienced moderate RLS symptoms. As many as 51.2% of respondents had poor quality of life, while the other 48.8% had good quality of life. The Spearman test results show that there is a significant relationship between the level of RLS and quality of life in CKD patients undergoing hemodialysis, with a significance value of 0.001 and a correlation coefficient (r) of 0.598.Conclusion: There is a significant relationship between the severity of Restless Legs Syndrome (RLS) and quality of life in chronic kidney disease patients undergoing hemodialysis. Therefore, it is recommended that health workers pay more attention to the symptoms of RLS in the management of hemodialysis patients, to improve their overall quality of life.